Smart technologies to enhance social connectedness in older people who live at home. (15th April 2014) - Morris, Meg E; Adair, Brooke; Ozanne, Elizabeth; Kurowski, William; Miller, Kimberly J; Pearce, Alan J; Santamaria, Nick; Long, Maureen; Ventura, Cameron; Said, Catherine M
<x xml:space="preserve">Abstract</x> Aim To examine the effectiveness of smart technologies in improving or maintaining the social connectedness of older people living at home. Methods We conducted a systematic review and critical evaluation of research articles published between 2000 and 2013. Article screening, data extraction and quality assessment (using the Downs and Black checklist) were conducted by two independent researchers. Results Eighteen publications were identified that evaluated the effect of smart technologies on dimensions of social connectedness. Fourteen studies reported positive outcomes in aspects such as social support, isolation and loneliness. There was emerging evidence that some technologies augmented the beneficial effects of more traditional aged‐care services. Conclusion Smart technologies, such as tailored internet programs, may help older people better manage and understand various health conditions, resulting in subsequent improvements in aspects of social connectedness. Further research is required regarding how technological innovations could be promoted, marketed and implemented to benefit older people.